Superfluidity near phase separation in Bose-Fermi mixtures - Enss, Tilman; Zwerger, Wilhelm (The European physical journal. B, Condensed matter and complex systems, 2009)
We study the transition to fermion pair superfluidity in a mixture of interacting bosonic and fermionic atoms. The fermion interaction induced by the bosons and the dynamical screening of the condensate phonons due to fermions are included using the nonperturbative Hamiltonian flow equations. We determine the bosonic spectrum near the transition towards phase separation and find that the superfluid transition temperature may be increased substantially due to phonon damping.